Radegast - Lankosz, Borys (Poland, 2008)
After many years, Lucille Eichengreen, a survivor from the Lodz ghetto, returns there to visit the places, streets and homes she remembers from her youth. On the walls of buildings, she can still find inscriptions of despair and horror left there by the inhabitants of the small Jewish ghetto during World War II.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films